Variability in deer diet and plant vulnerability to browsing among forests with different establishment years of sika deer - Yuzu Sakata; Nami Shirahama; Ayaka Uechi; Kunihiro Okano (PeerJ, 2021)
Increased ungulate browsing alters the composition of plant communities and modifies forest ecosystems worldwide. Ungulates alter their diet following changes in availability of plant species; however, we know little about how browse selection and plant community composition change with different stages of deer establishment. Here, we provide insight into this area of study by combining multiple approaches: comparison of the understory plant community, analysis of records of browsing damage, and DNA barcoding of sika deer feces at 22 sites in forests in northern Japan varying in when deer were first established. The coverage of vegetation and number of plant species were only lower at sites where deer were present for more than 20 years, while the difference in plant coverage among deer establishment years varied among plant species. Deer diet differed across establishment years, but was more affected by the site, thereby indicating that food selection by deer could change over several years after deer establishment. Plant life form and plant architecture explained the difference in plant coverage across establishment years, but large variability was observed in deer diet within the two categories. Integrating these results, we categorized 98 plant taxa into six groups that differed in vulnerability to deer browsing (degree of damage and coverage). The different responses to browsing among plant species inferred from this study could be a first step in predicting the short- and long-term responses of forest plant communities to deer browsing.